2015
DOI: 10.3758/s13421-015-0554-y
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and phonological contributions to short-term repetition and long-term cued sentence recall

Abstract: The function of verbal short-term memory is supported not only by the phonological loop, but also by semantic resources that may operate on both short and long time scales. Elucidation of the neural underpinnings of these mechanisms requires effective behavioral manipulations that can selectively engage them. We developed a novel cued sentence recall paradigm to assess the effects of two factors on sentence recall accuracy at short-term and long-term stages. Participants initially repeated auditory sentences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Generally, these results demonstrate that repetition ability is affected when the sequence of words is long and has no real meaning. Thus, both phonological and semantic (meaning) information contribute to sentence recall performance (see Meltzer et al, 2016 on the semantic contribution to short- and long-term sentence recall). Although researchers have studied the ability of patients with PPA to repeat words and sentences, none have systematically varied length and meaningfulness of stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these results demonstrate that repetition ability is affected when the sequence of words is long and has no real meaning. Thus, both phonological and semantic (meaning) information contribute to sentence recall performance (see Meltzer et al, 2016 on the semantic contribution to short- and long-term sentence recall). Although researchers have studied the ability of patients with PPA to repeat words and sentences, none have systematically varied length and meaningfulness of stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the discrepancy in spoken word comprehension between cohorts in our study contrasts with their very similar naming performance (see Table 2), arguing for an auditory rather than a primary semantic basis. It is further possible that any phonological input deficit is amplified by concomitantly more marked deficits of phonological production in English-speaking patients with nfvPPA and lvPPA, via impaired lexical predictive processing 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that Al-Sisi employed semantic repetition more than any other leader. Because the use of the semantic repetition has an explicit effect on the short term memory of the hearers (Meltzer et al, 2016), Al-Sisi might have tried to influence the public by varying the use of word relations that affect the short term memory of the audience. The most common used word relations in Al-Sisi's speech were binomials, synonyms and hyponyms.…”
Section: Findings and Discussionmentioning
confidence: 99%